2022
DOI: 10.3389/fimmu.2022.974916
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the pyroptosis-related genes and hub gene TP63 ceRNA axis in osteosarcoma

Abstract: Pyroptosis is a type of programmed cell death that is associated with tumor development, prognosis, and therapeutic response. The significance of pyroptosis-related genes (PRGs) in the tumor microenvironment (TME) remains unclear. We examined the expression patterns of PRGs in 141 OS samples from two different datasets and characterized the genetic and transcriptional changes in PRGs. Based on these PRGs, all OS samples could be classified into two clusters. We discovered that multilayer PRG changes were linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Hsa-miR-23a-3p was the only one significantly upregulated DE miRNA in both MG63 and 143B OS cells but not non-tumorigenic immortalized osteoblastic hFOB1.19 cells, which is consistent with the previous report that lncRNA GAS5 directly suppresses the expression of hsa-miR-23a-3p and inhibits the malignant progression of OS through PTEN/PI3K/AKT pathway ( Liu et al, 2020 ). In the aspect of bioinformatic analysis, pioneering researchers used the StarBase database to build a competing endogenous RNA (ceRNA) network and find a LAMTOR5-AS1/hsa-miR-23a-3p/TP63 regulatory axis which is involved in the malignant progress of OS ( Han et al, 2022 ). Meanwhile in our study, GO enrichment analysis showed that the target of hsa-miR-23a-3p was mainly involved in fatty acid metabolism pathway and muscle system process, which was closely related to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-23a-3p was the only one significantly upregulated DE miRNA in both MG63 and 143B OS cells but not non-tumorigenic immortalized osteoblastic hFOB1.19 cells, which is consistent with the previous report that lncRNA GAS5 directly suppresses the expression of hsa-miR-23a-3p and inhibits the malignant progression of OS through PTEN/PI3K/AKT pathway ( Liu et al, 2020 ). In the aspect of bioinformatic analysis, pioneering researchers used the StarBase database to build a competing endogenous RNA (ceRNA) network and find a LAMTOR5-AS1/hsa-miR-23a-3p/TP63 regulatory axis which is involved in the malignant progress of OS ( Han et al, 2022 ). Meanwhile in our study, GO enrichment analysis showed that the target of hsa-miR-23a-3p was mainly involved in fatty acid metabolism pathway and muscle system process, which was closely related to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Evidence shows that pyroptosis plays a pivotal role in the pathogenesis and progression of osteosarcoma, influencing responses to chemotherapy. 16 …”
Section: Introductionmentioning
confidence: 99%
“…15 Evidence shows that pyroptosis plays a pivotal role in the pathogenesis and progression of osteosarcoma, influencing responses to chemotherapy. 16 Given these advancements in molecular biology and bioinformatics, the identification of diagnostic and prognostic genomic biomarkers, including pyroptosis-related genes (PRGs), offers new opportunities for research. 17 The exact mechanism by which PRGs influence the development of osteosarcoma remains an area of active investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Competing endogenous RNAs (ceRNAs), initially proposed by Salmena and colleagues in 2011, was described as a complex regulatory network where mRNAs, lncRNAs, and other RNA species competed for the shared microRNA (miRNA) response elements (MREs) [49]. In particular, lncRNAs have been shown to act as ceRNAs, sequestering miRNAs, and subsequently influencing the expression of target mRNAs in the regulation of pyroptosis, which exerts a crucial effect on cancer progression and the TME [50][51][52].…”
Section: Introductionmentioning
confidence: 99%